2014
DOI: 10.21831/jpv.v4i2.2545
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh self-efficacy, lingkungan keluarga, dan lingkungan sekolah terhadap minat berwirausaha siswa SMK jasa boga

Abstract: Penelitian ini bertujuan untuk: 1) memperoleh gambaran tentang self-efficacy, lingkungan keluarga, lingkungan sekolah, dan minat berwirausaha pada siswa SMK Jasa Boga; 2) mengetahui pengaruh self-efficacy, lingkungan keluarga, dan lingkungan sekolah baik secara sendiri-sendiri maupun bersama-sama terhadap minat berwirausaha siswa SMK Jasa Boga. Penelitian ini merupakan penelitian ex-post facto. Populasi penelitian adalah seluruh siswa SMK kelas XII Kompetensi Keahlian Jasa Boga se kota Yogyakarta. Teknik penga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 1 publication
2
24
0
11
Order By: Relevance
“…The family environment positively and significantly influences entrepreneurial interest, as apparent from CR=4.770 and p<0.05. This result is in line with Adnan (2017), Marini & Hamidah (2014), Mustapha & Selvaraju (2015), and Wang et al (2018). Interest in pursuing self-employment can be grown only if the family also gives positive support (Altinay et al, 2012;Campopiano et al, 2016).…”
Section: Findings and Discussion Validity And Reliability Test Resultssupporting
confidence: 80%
“…The family environment positively and significantly influences entrepreneurial interest, as apparent from CR=4.770 and p<0.05. This result is in line with Adnan (2017), Marini & Hamidah (2014), Mustapha & Selvaraju (2015), and Wang et al (2018). Interest in pursuing self-employment can be grown only if the family also gives positive support (Altinay et al, 2012;Campopiano et al, 2016).…”
Section: Findings and Discussion Validity And Reliability Test Resultssupporting
confidence: 80%
“…Family and school environments are one of the factors that can contribute greatly to the career of students (Marini & Hamidah, 2014). Family and school factors in this case act as social support that can affect students in psychological aspects, productivity, and identity formation including career choice (Metheny & McWhirter, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…While Suryabrata (2006), suggested that the learning environment is divided into two, namely non-social environment and social environment. The social environment consists of the school environment, student social environment (community), and family environment, a nonsocial environment more to supporting learning process environment, such as physical learning building (school building), residence and location (house), learning tools, learning resources, weather conditions, lighting or lighting, and learning time (Shah, 2011;Marini, et al, 2014;Hayutika, & Subowo, 2016).…”
Section: Introductionmentioning
confidence: 99%